Maternal phthalate exposure and asthma, rhinitis and eczema in 552 children aged 5 years; a prospective cohort study - Camilla Jøhnk; Arne Høst; Steffen Husby; Greet Schoeters; Clara Amalie Gade Timmermann; Henriette Boye Kyhl; Iben Have Beck; Anna-Maria Andersson; Hanne Frederiksen; Tina Kold Jensen (BMC, 2020)
Abstract Background Prenatal phthalate exposure has been suggested to alter immune responses and increase the risk of asthma, eczema and rhinitis. However, few studies have examined the effects in prospective cohorts and only one examined rhinitis. We therefore studied associations between maternal urinary concentrations of phthalate metabolites and asthma, eczema and rhinitis in offspring aged 5 years. Methods From 552 pregnant women in the Odense Child Cohort, we quantified urinary concentrations of 12 phthalate metabolites in third trimester. We assessed asthma, rhinitis and eczema in their offspring at age 5 years with a questionnaire based on the International Study of Asthma and Allergies in Childhood (ISAAC), and conducted logistic regression adjusting for relevant confounders. Results 7.4% of the children had asthma, 11.7% eczema and 9.2% rhinitis. Phthalate exposure was low compared to previous cohorts. No significant associations between prenatal phthalate exposure and asthma were found. Odds ratios (ORs) of child rhinitis with a doubling in ΣDiNPm and di-2-ethylhexyl phthalate metabolite (ΣDEHPm) concentrations were, respectively, 1.15 (95% confidence interval (CI) 0.97,1.36) and 1.21 (CI 0.93,1.58). The OR of eczema when doubling ΣDiNPm was 1.24 (CI 1.00,1.55), whereas the OR of using medicine against eczema when doubling a di-ethyl phthalate (DEP) metabolite was 0.81 (CI 0.68,0.96). Conclusion The lack of association between maternal phthalate exposure and asthma in the offspring may be due to low exposure and difficulties in determining asthma in 5-year-olds. The higher odds of rhinitis may raise public concern but further research in larger cohorts of older children is warranted.